Indigenous Utilization of Plant Biodiversity in Malakkheil-Kotkay Village, District Shangla, Pakistan: Plant Biodiversity in Shangla District - Hadi, Fazal; Khan, Shafqat Ali; Ibrar, Muhammad; Samreen, Ulfat (Biological Sciences - PJSIR, 2019)